USED OF MARBALE WASTE POWER FOR REPLACEMENT OF CEMENT - Husain, DR.M.; .I, ChavanF; Navale, Kalyani (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
This project describes the feasibility of using the marble sludge dust in concrete production as partial replacement of cement. In INDIA, the marble and granite stone processing is one of the most thriving industry[6] the effects if varying marble dust contents on the physical and mechanical properties of fresh and hardened concrete have been investigated. Slump and air content of fresh concrete and absorption and compressive strength of hardened concrete were also investigated. Test results show that this industrial bi product is capable of improving hardened concrete performance up to 10%, Enhancing fresh concrete behavior and can be used in architectural concrete mixtures containing white cement. The compressive strength of concrete was measured for 7 and 28 days. In order to evaluate the effects of marble dust on mechanical behavior, many different mortar mixes were tested